Polymer‐delivered subcutaneous leuprolide acetate formulations achieve and maintain castrate concentrations of testosterone in four open‐label studies in patients with advanced prostate cancer. (16th April 2016) - Shore, Neal D.; Chu, Franklin; Moul, Judd; Saltzstein, Daniel; Concepcion, Raoul; McLane, John A.; Atkinson, Stuart; Yang, Alex; Crawford, E. David
Abstract : Objective: To determine whether luteinising hormone‐releasing hormone (LHRH) agonist, ATRIGEL ® polymer‐delivered, subcutaneous, leuprolide acetate (ADSC‐LA), formulations suppressed serum testosterone to concentrations of ≤20 ng/dL. Patients and Methods: Data from four open‐label, fixed‐dose studies were evaluated. Male patients aged 40–86 years with advanced prostatic adenocarcinoma, whom had not undergone prior androgen‐deprivation therapy (ADT), were treated with a depot formulation of ADSC‐LA: 7.5 mg (1‐month, 120 patients), 22.5 mg (3‐month, 117 patients), 30 mg (4‐month, 90 patients), or 45 mg (6‐month, 111 patients). Serum testosterone was sampled at screening, baseline, 2, 4, 8 h after dosing, 1, 2, 3, and 7 days, and every week until the next dose, at which time, the sampling schedule repeated until the end of study (24 weeks for 1‐ and 3‐month formulations, 32 weeks for 4‐month, and 48 weeks for the 6‐month). The primary analyses were mean serum testosterone concentrations and proportion of patients who achieved concentrations of ≤20 ng/dL. Results: The mean (SE) serum testosterone concentrations at the end of study were consistently ≤20 ng/dL in each study, at 6.1 (0.4), 10.1 (0.7), 12.4 (0.8), and 12.6 (2.1) ng/dL for the 1‐, 3‐, 4‐, and 6‐month formulations, respectively. A high proportion of patients (94%, 90%, 92%, 96% for the 1‐, 3‐, 4‐, and 6‐month formulations, respectively) achieved testosterone concentrations of ≤20 ng/dL within 6 weeks, and 90–97% of patients in all studies maintained concentrations of ≤20 ng/dL from weeks 6–24. Conclusions: Recent studies have shown improved outcomes in patients with prostate cancer who consistently attained a more rigorous level of testosterone suppression (≤20 ng/dL) with ADT than the historical standard (≤50 ng/dL). All doses of ADSC‐LA rapidly achieved and maintained mean serum testosterone to the more rigorous target concentration of ≤20 ng/dL. These data suggest that ADSC‐LA delivers equivalent testosterone suppression as achieved by surgical castration.